Peranan Garbage Management Plan dalam Pencegahan Pencemaran di atas Kapal KM. Tanto Berkat - Mohammad Farhan Resa Fathoni Shofwan; Anak Agung Istri Sri Wahyuni; Maulidiah Rahmawati; I’ie Suwondo (Pusat riset dan Inovasi Nasional, 2025)
This research aims to explore and analyze the garbage management plan implemented on board ships. In this context, the author conducts direct observation to understand the problems encountered in executing the plan. Through firsthand experience, the author can identify various obstacles that may arise, especially those related to non-compliance with existing official procedures and regulations.The data collection methods used in this study include several approaches, allowing the author to obtain comprehensive information regarding waste management practices on ships. By using appropriate analytical techniques, the author seeks to find solutions to the problems faced in garbage management and provide applicable recommendations to improve the plan's effectiveness.The results of this research are expected to provide better insights into the challenges faced in waste management within the maritime environment, and to encourage the development of better policies for waste management on board ships. Thus, this research not only contributes to academic literature but also provides practical benefits for the shipping industry and environmental management.